EDUKASI DAN SKRINING HEPATITIS B PADA WARGA BINAAN PEMASYARAKATAN (WBP) DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA KASONGAN, KALIMANTAN TENGAH - Lia Sasmithae; Dian Mutia Sari; Tisha Patricia; indra Perdana (Jurnal Pengabdian Kampus, 2022)
Hepatitis B is a liver disease caused by the Hepatitis B virus (HBV). The mode of HBV transmission is parenteral, vertical (transmission), maternal (mother)-neonatal (fetus), or horizontal (very close and prolonged contact between individuals, sexual, iatrogenic, and sharing needles). Prison inmates (WBP) in Narcotics Prisons attributed with a high-risk factor of being infected with the hepatitis B virus. Due to the use of narcotics and illegal drugs by sharing needles, piercings, tattoos, and having free sexual intercourse because of wrong behavior. The impact caused by infection with the hepatitis B virus can cause advanced diseases such as cirrhosis of the liver and liver cancer. Therefore the activities carried out by the community service team from the Faculty of Medicine at the University of Palangkaraya. The target, Residents of the Class IIA Narcotics Correctional Institution, Kasongan. These community service aim to convey education in the form of counseling related to symptoms, transmission methods, prevention, treatment, and various health services related to hepatitis B, as well as conducting HBsAg examination screening of WBP and distributing X-banners to the prison.